Sweet, reinforced, and fortified wines : grape biochemistry, technology, and vinification - Mencarelli, F. (Fabio); Tonutti, P. (Pietro); Wiley eBooks (Chichester, West Sussex ; Hoboken, NJ : Wiley-Blackwell, 2013)
Wines from Grape Dehydration is the first of its kind in the field of grape dehydration - the controlled drying process which produces a special group of wines. These types of wine are the most ancient, made in the Mediterranean basin, and are even described in Herodotus. Until few years ago, it was thought that these wines - such as Pedro Ximenez, Tokai, Passito, and Vin Santo - were the result of simple grape drying, because the grapes were left in the sun, or inside greenhouses that had no controls over temperature, relative humidity or ventilation. But Amarone wine, o.
pt. 1. History -- pt. 2. Vineyard management, on-vine and postharvest grape dehydration, vinification -- pt. 3. The wines -- pt. 4. Market and marketing.
Includes bibliographical references and index.
John Wiley and Sons
Keywords: Wine and wine making -- Chemistry; Grapes; Fortified wines; Fortified wines; Grapes; Wine and wine making -- Chemistry; TECHNOLOGY & ENGINEERING -- Food Science; Fortified wines; Grapes; Wine and wine making -- Chemistry; Electronic books